Does faster internet increase exports? Evidence from New Zealand - Sanderson, Lynda (OECD Publishing, 2022)
This paper explores the relationship between adoption of ultra-fast broadband (UFB) and the export propensity of New Zealand firms. Previous literature have shown that the Internet facilitates exports by reducing search costs and informational frictions in establishing trade relationships. However, the role of faster Internet that enables the use of more recent, advanced, data-intensive digital technologies has not been well explored. This paper shows empirically that adoption of fibre broadband is associated with a higher propensity to enter exporting by New Zealand firms, suggesting that faster Internet has an additional role over traditional Internet in facilitating exporting. The paper also shows that firms that were already using the Internet more intensively prior to adopting fibre experience a stronger increase in export propensity following fibre adoption than those with less intensive Internet use, and that the positive relationship between fibre uptake and exporting is primarily observed among services firms. Instrumental variable analysis to assess the causal relationship between fibre uptake and exporting suggests that the higher export entry among fibre users is driven by self-selection of firms with higher export propensity into fibre uptake
Keywords: Economics; New Zealand